Northwest History. Alaska, Glaciers. United States. (1937)
Groaning Glacier Like Earthquake. GROANING GLACIER LIKE EARTHQUAKE By Associated Press. FAIRBANKS, Alaska, Feb. 16.— Fog made the Black Rapids glacier invisible today, but Mrs. H. E. Revell, whose home is in the path of the swift-moving ice wall, telephoned that its roaring, groaning movement was plainly audible and that the crash of toppling tons of ice shook the house on its foundation. "All through the night and day, the ceaseless roar and groaning dins in our ears," she told an interviewer over a 130-mile telephone "Heavy fogs blanketed the valley today, making the glacier invisible, but we hear thundering crashes periodically, and our house vibrates at times, especially in the early evening." The glacier, about 30 miles long and fed by two branches, had been* receding for ages until last October when the fall rains were followed by a swift forward movement. The glacier has advanced 3% to 5 miles since fall, its speed recently accelerated by an earthquake. Mr. and Mrs. Revell and scientists who flew to study the glacier last week before thick weather set in, believe the glacier will spread and scatter out over the valley instead of damming the river and engulfing the Revells' roadhouse, but the Revells are packed and ready to move at an instant's notice.